Biomedical parameters assessed in pregnant mice receiving oral commercial nanosilver preparations - Marina N. Gapon; E. A. Ivanova; T. I. Tverdokhlebova; А. V. Kantaria; Z. T. Tagirov; I. A. Loginov; E. A. Gapon (Инфекция и иммунитет)
The aim of the work was to determine the safety of oral commercial colloidal nanosilver preparations during mouse pregnancy by assessing microbiota and local colonic nonspecific resistance; pregnancy course and outcome; morphology of vital organs — kidneys, liver, brain in pregnant mice and paired offspring. Microbiological, biochemical, and histological research methods were used in the work. Empirically selected commercial colloidal nanosilver preparations (“Ajenta”, “Vitargol”) recommended for internal use in humans at a therapeutic dose were used in an in vivo experiment by 30-day watering of pregnant mice. As a result, the large intestine microbiome balance was restored due to decreased in number of pathogens: enterobacteria, Staphylococcus and Candida. In the coprofiltrates of both groups of mice receiving both “Adjenta” and “Vitargol”, the state of local nonspecific resistance showed impaired local antiradical protection. If after “Adjenta” therapy there was an imbalance in antioxidant enzyme system, when the activity of superoxide dismutase was 1.5 times higher than control level, and catalase activity was 2 times lower contributing to higher level of peroxidation product — malondialdehyde by 2.6 times, then after “Vitargol” therapy activity of superoxide dismutase and catalase was only 43% and 25%, and the amount of malondialdehyde peaked reaching 431%. Microscopic examination of all organ biopsies from mice receiving commercial colloidal nanosilver preparations “Ajenta” and “Vitargol” revealed no fundamental differences. At the same time, morphological changes in tissues were found in all animals: granular dystrophy of hepatocytes, nephrocytes of the proximal and distal tubules, perinuclearly in liver preparations there is a cytoplasm enlightenment in some liver cell types. In all brain samples, there is moderate perivascular-pericellular edema, vascular fullness, neuron dystrophy. However, breast-fed mouse pup liver histological examination from paired female mice after oral Vitargol intake revealed no negative changes. Despite the fact that the processes of gestation and childbirth in mice proceeded normally, the results of the study indicate insufficient safety of the selected drugs for oral use during pregnancy.